Mengokohkan Harmoni Beragama: Transformasi Pendidikan dalam Membangun Toleransi - Sugiarto, Lilik; Zulkarnain, Nanang Rahmat; Bayhaqi, Silmi (Al Mabhats : Jurnal Penelitian Sosial Agama, 2023)
Abstract: Indonesia is a country rich in culture and heritage. The Islamic values as a main component of education play a role in shaping the character of students. Unfortunately, being educated does not necessarily guarantee tolerance. Therefore, there is a need for educational system reform to create graduates who are tolerant and moderate. This research uses a qualitative approach with literature review techniques. The data is obtained from references such as books and research journals. The data is processed from 40 primary references. The results of the study show a series of strategic efforts in educational reform focused on several aspects, namely the reform of the education service system, curriculum and learning reform, and the reform of the educational environment and digital culture.   Abstrak: Indonesia negara yang kaya akan kultur dan budaya. Nilai Islam sebagai komponen utama pendidikan berperan dalam membentuk karakter peserta didik.. Sayangnya, berpendidikan belum tentu toleran, untuk itu perlu reformasi sistem pendidikan untuk menciptakan lulusan yang toleran dan moderat. Penelitian ini menggunakan pendekatan kualitatif dengan teknik kepustakaan. Data diambil dari rujukan berupa buku dan jurnal penelitian. Data diolah dari rujukan primer berjumlah 40 rujukan. Hasil penelitian menunjukkan serangkaian upaya strategis reformasi pendidikan yang dilakukan terfokus pada beberapa aspek yaitu reformasi sistem layanan pendidikan, reformasi kurikulum pembelajaran dan reformasi lingkungan pendidikan dan budaya digital.